How do GPs and patients experience Persistent Frequent Attendance in primary care? A qualitative study - Stubley, Shelly (ML) (2021)
Persistent frequent attendance in primary care in the UK can be seen as problematic for the health service as persistent frequent attenders (PFAs) take up a disproportionate amount of time and resources and impact on the clinical workload of GPs (General Practitioners) (Smits, 2009 & Smits, 2013). These patients can be frustrating and difficult for GPs to manage particularly when frequent attendance continues for longer periods of time (Lin et al 1991, Hanel et al 2009).